Village Government Supervision in the Management of Danau Biru Geotourism in North Kolaka - Fait, Taslim; Irabiah; Badia, Juslan; Septiana, Anis Ribcalia (Teras Kampus, 2025)
This study aims to analyze the supervisory function by the Walasiho Village Government in the management of Danau Biru Geotourism in Walasiho Village, Wowo District, North Kolaka Regency, Southeast Sulawesi. The research method uses a qualitative descriptive approach. Preparations for research, data collection and analysis will be carried out in January-August 2025. Primary data was obtained from the results of interviews with informants, namely the Head of Marketing of the North Kolaka Tourism Office, the Head of Walasiho Village, business actors, and visitors. Observations at the research site and Focus Group Discussion (FGD) with employees at the North Kolaka Tourism Office office completed the research data. The secondary data comes from articles, books, and documents from the North Kolaka Tourism Office and the Walasiho Village Government. Data analysis is in the form of data condensation, data presentation, and drawing conclusions according to the Miles, Huberman, and Saldana (2014) model. The results of the study show that the supervision carried out by the village government aims to ensure the maximum deposit of visitor levies as the village's contribution to the local original income (PAD) of North Kolaka Regency. Meanwhile, the supervisory function does not yet have standard standards, comprehensive performance indicators, gaps with ideal standards, and corrective mechanisms that are not yet systematic. In conclusion, the supervisory function of the Walasiho Village Government in the management of Danau Biru Geotourism is not ideal so that it has the potential to hinder the sustainability of tourism management.